Cyclooxygenase Expression and Platelet Function in Healthy Dogs Receiving Low‐Dose Aspirin. (26th December 2012) - Dudley, A.; Thomason, J.; Fritz, S.; Grady, J.; Stokes, J.; Wills, R.; Pinchuk, L.; Mackin, A.; Lunsford, K.
<x xml:space="preserve">Abstract</x> Background Low‐dose aspirin is used to prevent thromboembolic complications in dogs, but some animals are nonresponsive to the antiplatelet effects of aspirin ("aspirin resistance"). Hypothesis/Objectives That low‐dose aspirin would inhibit platelet function, decrease thromboxane synthesis, and alter platelet cyclooxygenase (COX) expression. Animals Twenty‐four healthy dogs. Methods A repeated measures study. Platelet function (PFA‐100 closure time, collagen/epinephrine), platelet COX‐1 and COX‐2 expression, and urine 11‐dehydro‐thromboxane B2 (11‐dTXB2) were evaluated before and during aspirin administration (1 mg/kg Q24 hours PO, 10 days). Based on prolongation of closure times after aspirin administration, dogs were divided into categories according to aspirin responsiveness: responders, nonresponders, and inconsistent responders. Results Low‐dose aspirin increased closure times significantly (62% by Day 10, P < .001), with an equal distribution among aspirin responsiveness categories, 8 dogs per group. Platelet COX‐1 mean fluorescent intensity (MFI) increased significantly during treatment, 13% on Day 3 (range, −29.7–136.1%) (P = .047) and 72% on Day 10 (range, −0.37–210%) (P < .001). Platelet COX‐2 MFI increased significantly by 34% (range, −29.2–270%) on Day 3 (P = .003) and 74% (range, −19.7–226%) on Day 10 (P < .001). Urinary 11‐dTXB2 concentrations significantly (P = .005, P < .001) decreased at both time points. There was no difference between aspirin responsiveness and either platelet COX expression or thromboxane production. Conclusions and Clinical Importance Low‐dose aspirin consistently inhibits platelet function in approximately one‐third of healthy dogs, despite decreased thromboxane synthesis and increased platelet COX expression in most dogs. COX isoform expression before treatment did not predict aspirin resistance.